Electrochemical sensor for the determination of dimetridazole using a 3D Cu2O/ErGO-modified electrode. Issue 27 (28th June 2018) - Ma, Xionghui; Li, Jianping; Luo, Jinhui; Liu, Chunhua; Li, Shuhuai
Abstract : Three-dimensional Cu2 O/ErGO was prepared on a GCE. The voltammetric behavior of DMZ was investigated by using a modified electrode through CV and DPV. The proposed method is suitable for DMZ detection because of its low cost, simplicity and accuracy. Abstract : A three-dimensional Cu2 O/electrochemically reduced graphene (ErGO)-modified electrode was developed for the determination of dimetridazole. Cu2 O/GO was initially prepared using a modified solvothermal method, and the 3D structure was constructed by electrodepositing a Cu2 O/GO dispersion on a glassy carbon electrode in the presence of lithium perchlorate. The enhanced electrocatalytic reduction of dimetridazole was confirmed, and the electrochemical reduction reaction was found to be a typical adsorption-controlled process. Our results revealed that the response to dimetridazole was linear in the concentration range of 30–150 nmol L −1 and the detection limit was 3.64 nmol L −1 . The prepared electrode was also employed to detect dimetridazole in an egg sample, thereby indicating its potential practical application.